What fraction of the Pacific and Indian oceans' deep water is formed in the Southern Ocean? - J. W. B. Rae; W. Broecker (Biogeosciences, 2018)
In this contribution we explore constraints on the fractions of deep water present in the Indian and Pacific oceans which originated in the northern Atlantic and in the Southern Ocean. Based on PO4* we show that if ventilated Antarctic shelf waters characterize the Southern contribution, then the proportions could be close to 50–50. If instead a Southern Ocean bottom water value is used, the Southern contribution is increased to 75 %. While this larger estimate may best characterize the volume of water entering the Indo-Pacific from the Southern Ocean, it contains a significant portion of entrained northern water. We also note that ventilation may be highly tracer dependent: for instance Southern Ocean waters may contribute only 35 % of the deep radiocarbon budget, even if their volumetric contribution is 75 %. In our estimation, the most promising approaches involve using CFC-11 to constrain the amount of deep water formed in the Southern Ocean. Finally, we highlight the broad utility of PO4* as a tracer of deep water masses, including descending plumes of Antarctic Bottom Water and large-scale patterns of deep ocean mixing, and as a tracer of the efficiency of the biological pump.